Problemy travmatologii v sovremennom sporte - Kovalenko, Ju. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
In modern sports the traumatology problems are noted for their specificity concerning the character and localization of damages, ways of their estimation and recovery. The traumatic-orthopedic diseases, submitting to the general mechanisms of appearance and development of traumas, or distinguished in their varietiveness, recovery speed, and also psychological moments - mutual understanding between patients and the treating personnel lay In the basis of the damages.